Measurement of the spontaneous motility in vitro of the floor of the reticular sulcus in cattle (Revista Española de Fisiología, 1989)
The bases and the parameters which define the smooth muscle spontaneous motility of the reticular groove floor in cattle have been established.The study has been carried out in 27 esophageal grooves in a classic organ bath technique.The results show a recognizable own spontaneous motility with two kinds of contractions: high tension ones and others with smaller contraction intensity.The young animal parameter values are different from those of grown-up ones.In adults, these values depend on the muscular dissection belt.